The Ecuadorian Tourism Sector: Smart Tourism Initiative and the Impact in the Economy of Ecuador - Leon, Paulina; Fuentes, Rafael; Guevara, Antonio (Journal of Posthumanism, 2025)
Technological advances have not only ventured to efficiently boost industrial production. In recent years it has helped improve the provision of services both in person and remotely. This document analyzes the advantages that the use of these technological instruments has provided. In favor of the Ecuadorian tourism sector, the empirical evidence agrees on a positive relationship between technology and tourism; Using generalized least squares econometric models to obtain a reliable and concise estimate determines the existence of a positive relationship of variables in the Ecuadorian case within the last 15 years. However, as there is a long way to go, the work of both the Public authorities and private sector actors must be consolidated in terms of infrastructure, training and innovation to obtain positive effects for society in general.